PERSPEKTIF EKONOMI DAN BISNIS ISLAM MENGENAI PENGARUH INDEKS PEMBANGUNAN MANUSIA, PERTUMBUHAN EKONOMI, BELANJA MODAL, DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP KEMISKINAN DI PROVINSI JAWA TIMUR TAHUN 2002-2021 - Kusumaningrum, Ria; Kulsum, Umi; Aisyah Hafsari, Marsha Siti; Ananda, Della Rizki (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Poverty is defined as one of the recurring core problems in human life. Poverty is a problem that is often encountered but never resolved in both developing and developed countries. Understanding the extent to which the Human Development Index (IPM), Economic Growth (GDP), Capital Expenditure, and the Open Unemployment Rate affect the poverty rate in East Java Province from 2002-2021 are all the overall objectives of this research. This analysis uses multiple regression models using time series data. The results of this study show that the HDI and capital expenditures have a significant negative effect on the poverty rate in East Java. Meanwhile Economic Growth (GDP) and Open Unemployment Rate (TPT) have a positive and significant influence on Poverty in East Java.